Simplified Perovskite Solar Cell with 4.1% Efficiency Employing Inorganic CsPbBr3 as Light Absorber. Issue 20 (17th April 2018) - Duan, Jialong; Zhao, Yuanyuan; He, Benlin; Tang, Qunwei
Abstract: Perovskite solar cells with cost‐effectiveness, high power conversion efficiency, and improved stability are promising solutions to the energy crisis and environmental pollution. However, a wide‐bandgap inorganic–semiconductor electron‐transporting layer such as TiO2 can harvest ultraviolet light to photodegrade perovskite halides, and the high cost of a state‐of‐the‐art hole‐transporting layer is an economic burden for commercialization. Here, the building of a simplified cesium lead bromide (CsPbBr3 ) perovskite solar cell with fluorine‐doped tin oxide (FTO)/CsPbBr3 /carbon architecture by a multistep solution‐processed deposition technology is demonstrated, achieving an efficiency as high as 4.1% and improved stability upon interfacial modification by graphene quantum dots and CsPbBrI2 quantum dots. This work provides new opportunities of building next‐generation solar cells with significantly simplified processes and reduced production costs. Abstract : A simplified perovskite solar cell with 4.1% efficiency employing CsPbBr3 as a light harvester is made by a solution‐processable multistep method.